Modelling and optimization of flexible manufacturing systems - Granados Fernández, Víctor Hugo (2012)
The Lagrangian relaxation method for solving a Mixed-Integer Linear Problem was implemented in order to improve the current TEMPO-PSI team exible manufacturing system solutions, available at the AIP-primeca pole in University of Valenciennes, France. The MILP optimization model, from TEMPO-PSI team, can not guarantee good results when the amount of jobs in the manufacturing system increases due to the growth in the number of variables of the model. A study on the optimization model was conducted with the objective to nd the candidate constraints for Lagrangian relaxation. A comparative study is made between the initial model solutions and Lagrange-relaxed model solutions. The results of the present research indicate that the use of the Lagrangian relaxation method on the scheduling problems could have advantages in obtaining better solutions. Um método relaxação lagrangeana para resolver um problema de Programação Misto- Inteira Linear foi implementado com o objetivo de melhorar as soluções actuais dos sistemas de manufatura exíveis da equipa TEMPO-PSI, disponível no laboratório AIPprimeca da Universidade de Valenciennes, França. O modelo de optimização MILP, da equipa TEMPO-PSI, não consegue garantir bons resultados quando a quantidade de operações no sistema de manufactura aumenta, devido ao crescimento do número de variáveis do modelo. O estudo do modelo de optimização foi levado a cabo com o objectivo de encontrar as restrições candidatas para a relaxação Lagrangeana. O estudo comparativo é feito entre as soluções iniciais do modelo e as soluções do modelo relaxado com o método de Lagrange. Os resultados da presente investigação indicam que o uso de método da relaxação Lagrangeana nos problemas de escalonamento de tarefas poderá ter vantagens na obtenção de melhores soluções.